(untitled) (The Planet, 2023)
Background: Malpresentation is when the fetus is not facing head-first down the birth canal as birth approaches. The most common type of mal-presentation is breech-when the fetus’s bottom or feet are facing downwards. Antenatal checkups may be one of the methods of it. Aim of the study:The aim of this study was to assess the antenatal checkup status of pregnant mothers diagnosed with fetal mal-presentation. Methods&Materials: This was a cross-sectional descriptive study. The study was conducted in the Department of Obstetrics & Gynecology, Rangpur Medical College Hospital, Rangpur, Bangladesh during the period from July 2003 to June 2004. In 100 mothers diagnosed with fetal mal-presentation were enrolled in this study. Results: In this study, most of the respondents (76%) had not received any antenatal cheek-up, 17% got irregular antenatal cheek-up and only 7% received regular antenatal care. As the frequency distribution of the study 46% were with breech buttock, 26% with shoulder presentation, 12% with breech footling, 11% with the transverse lie, 2% with cord presentation, and 1% with brow and face in each. Among total cases, 86% did not do any ultra-sonogram, in 13% of cases ultrasonogram revealed breech presentation, and in 1% of the case revealed brow presentation. Conclusion: Malpresentation during pregnancy is a very common obstetrical problem in Bangladesh. As per the findings of this study, we can conclude thatcomplications of mal-presentation can be prevented by regular antenatal check-ups to detect all mispresented pregnant women and advise them to deliver in a well-equipped hospital.